2018
DOI: 10.1017/s1751731117003305
|View full text |Cite
|
Sign up to set email alerts
|

Long-term implications of feed energy source in different genetic types of reproductive rabbit females: III. Fitness and productivity

Abstract: The specialization process associated with genetic selection could be associated with functional disorders, affecting the reproductive success of females (fitness). We hypothesized that by modulating energy acquisition and allocation of females we could balance productivity and reproductive success. To test this hypothesis, we used 203 rabbit females belonging to three genetic types: H (n=66) maternal line specialized in prolificacy, LP (n=67) generalist maternal line, R (n=70) paternal line specialized in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It is well known that the development of rabbit females is related to the development of fetuses in the first reproductive cycles, i.e., for nulliparous and primiparous animals [38]. This agrees with the increment in PFT from 12 weeks of age until the second delivery.…”
Section: Discussionsupporting
confidence: 84%
“…It is well known that the development of rabbit females is related to the development of fetuses in the first reproductive cycles, i.e., for nulliparous and primiparous animals [38]. This agrees with the increment in PFT from 12 weeks of age until the second delivery.…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that fat-enriched diets favour milk yield, whereas starch-enriched diets favour body reserve gain (Pascual et al, 2003). This is the first of three consecutive scientific papers that aim to evaluate the hypothesis that the effect of energy source of the diet varies with the genetic type, having implications in the way each genetic type acquires and allocates resources over time, their immunological status or their fitness and productivity (see companion papers Arnau-Bonachera et al, 2017;Penadés et al, 2017). Specifically, in the present work we studied: (i) the way three genetic types, widely differing in their genetic background, acquire and allocate resources.…”
Section: Introductionmentioning
confidence: 99%
“…H rabbit does are very dependent of their body condition, as they need to be able to feed very large litters. However, excessive fat deposits can also be counterproductive, as they diminish fertility and increase mortality (Arnau-Bonachera et al, 2017a and2017b). On the contrary, LP animals do not depend on their body condition as much as H animals, mainly because they have developed several different mechanisms to modulate their responses and keep the energy homeostasis balance without reducing their fertility, while being able to maintain most of their litter alive until weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the evidenced impact of genetic selection on the robustness of the animal, it has also been suggested that the use of a fat-enriched lactation diet could contribute to improving the maturity of the immune system of young rabbits at weaning (García-Quirós et al, 2014) and, therefore, their general health status towards the growing period. In this conceptual framework, this is the second of three consecutive papers (see companion papers Arnau-Bonachera et al, 2017a and2017b) that were designed to provide a context in which animals from three different genetic types and fed with two distinct dietsbut housed and bred in the same conditions-could be systematically studied and compared throughout their reproductive life (from the first artificial insemination to the sixth parturition). In that context, this paper is mainly focused on the study of the immunological status of the animals.…”
Section: Introductionmentioning
confidence: 99%